Authentic Drug Usage and Tracking with Blockchain Using Mobile Apps - Benita K, Ruby; Kumar S, Ganesh; B, Murugamantham; A, Murugan (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Tracking drugs became more difficult using the centralized architecture. Decentralized architecture using blockchain technology overcomes the difficulties faced by the centralized network like availability and recovery. Avoiding duplicate or fake drugs created by fake manufacturers is a big challenge in the centralized network. Authentic stock is managed and the supply chain is tracked efficiently using this blockchain technology. This is addressed by using the smart contract which helps to track the movement of drugs from manufacturer to supplier, supplier to the reseller, reseller to pharmacies and finally pharmacies to patient. By default, duplicate drugs or fake drugs are completely avoided by using the blockchain technology. Patients buy drugs without any prescription and it creates a lot of problems in real life. So, Patients cannot buy drugs without authenticated doctor’s prescriptions with the help of a QR Code scanner attached with the prescription which will be implemented using a mobile application and cannot buy excess drugs which might lose someone’s life. With the help of inventory management, the maximum limit of drugs to avoid overdose and pharmacies cannot sell those overdose drugs. Consulting a doctor before buying a drug for even a simple illness is important and it is tracked by using prescriptions provided by authentic doctors. In this project, these challenges are addressed using the smart contract which is written in solidity language and runs on a public ethereum network.